Tobacco Use and Body Mass Index as Predictors of Outcomes in Patients Undergoing Breast Reduction Mammoplasty. Issue 4 (October 2015) - Karamanos, Efstathios; Wei, Benjamin; Siddiqui, Aamir; Rubinfeld, Ilan
Abstract : Background: Breast reduction mammoplasty accounts for more than 60, 000 procedures annually, but the literature is still sparse on outcomes, especially beyond the single institution perspective. The aim of this study was to seek a broader view by study breast reduction outcomes in the National Surgical Quality Improvement Program database. Methods: The National Surgical Quality Improvement Program data set was queried for the Current Procedural Terminology code 19318 from the years 2005 to 2010. The principal outcomes measured were wound complications, surgical site infections, and reoperations. Univariate and multivariate analysis was performed to identify significant relationships. Results: A total of 2779 patients were identified. The mean age was 42.7 (14.1) years and the mean body mass index (BMI) was 31.6 (7.0) kg/m 2 . Tobacco use was associated with a higher rate of reoperation ( P = 0.02). Body mass index was identified as an independent risk factor for wound complications (odds ratio, 1.85, P = 0.005). Patients with BMI greater than 40 kg/m 2 were significantly more likely to develop postoperative wound complications ( P = 0.02). Conclusions: This study represents the largest sample on breast reduction in the literature. Age and surgeon specialty did not correlate with negative results. In contrast, tobacco use and BMI were associated with worse breast reduction outcomes.